2015
DOI: 10.2319/071614-498.1
|View full text |Cite
|
Sign up to set email alerts
|

Pain experience during initial alignment with three types of nickel-titanium archwires: A prospective clinical trial

Abstract: Objective: To clinically evaluate the pain intensity during the week following initial placement of three different orthodontic aligning archwires. Materials and Methods: A consecutive sample of 75 patients requiring upper and lower fixed orthodontic appliances were alternately allocated into three different archwires (0.014-inch superelastic NiTi, 0.014-inch thermoelastic NiTi or 0.014-inch conventional NiTi). Assessments of pain/discomfort were made on a daily basis over the first 7-day period after bonding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 23 publications
4
36
1
5
Order By: Relevance
“…Pain intensity levels reported here were low overall compared with those reported in studies examining pain during conventional RME treatment 10,13 and pain in the first week with a fixed appliance, [7][8][9] indicating that RME treatment, both conventional and skeletal, is well accepted by patients in this young age group. Analgesic consumption was consequently low.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…Pain intensity levels reported here were low overall compared with those reported in studies examining pain during conventional RME treatment 10,13 and pain in the first week with a fixed appliance, [7][8][9] indicating that RME treatment, both conventional and skeletal, is well accepted by patients in this young age group. Analgesic consumption was consequently low.…”
Section: Discussioncontrasting
confidence: 74%
“…To minimize these dental side effects, which likely increase the risk of relapse, skeletally anchored RME appliances have been introduced. [4][5][6] Pain and discomfort are well-known side effects of orthodontic treatment with fixed appliances, [7][8][9] but few studies [10][11][12] have explored pain and discomfort during RME treatment. These few studies have concluded that most children undergoing RME report pain, which generally occurs during the initial phase and diminishes thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…ICON is an index that evaluates the severity of malocclusion among patients (Liao et al , ). Our results revealed that ICON was not significantly correlated with orthodontic pain levels ( β = −0.1, 95% CI: −0.2~0.1), which was consistent with those published previously (Abdelrahman et al , ; Markovic et al , ). Moreover, we failed to find any correlation between age and orthodontic pain levels.…”
Section: Discussionsupporting
confidence: 93%
“…Despite that, there are controversial results about the correlation between the irregularity index and the perception of pain. Some studies found that there is no correlation [52][53][54], but a recent one found that crowding is a risk factor, and with each increase in crowding, there is a 1.10 times increase in painful sensation [55].…”
Section: Discussionmentioning
confidence: 99%